The Importance of Educator's Commitment in Improving Students' Learning Independence After the Covid-19 Pandemic: Pentingnya Komitmen Pendidik dalam Meningkatkan Kemandirian Belajar Peserta Didik Pasca Pandemi Covid-19 - Amelia, Viona; Rindaningsih, Ida (Indonesian Journal of Education Methods Development, 2023)
This research was conducted with the intent and purpose to analyze comitment of professional teachers in the independent learning of student after the Covid-19 pandemic at SD Muhammadiyah 2 Sidoarjo and analyze independent learning of student after the Covid-19 pandemic at SD Muhammadiyah 2 Sidoarjo. This research is a qualitative approach research with descriptive type. The subjects in this study were teachers and students in class IV Al-Farabi. Data collection techniques in this research are interviews, observation and documentation. Data analysis in this research is data reduction, data presentation and conclusion drawing. Testing the data in this study using triangulation techniques obtained from interviews, observations, and documentation. The results obtained from the first study are the independent learning of students in class IV Al-Farabi which is considered very good in terms of the attitude of independence from the aspects of self-confidence, responsibility, discipline, and honesty. The results of the secound research study are the role of professional teachers in the independence of students' learning by using varied learning methods or media, providing learning evaluations to students according to the material presented, helping students who experience internal and external problems, motivating the enthusiasm of their students. to learn to find new understanding both individually and in groups and the last to try to develop their insight and knowledge.